2022
DOI: 10.1093/femsec/fiac092
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of root-associated N2O-reducing communities of annual crops is governed by selection for nosZ clade I over clade II

Abstract: The rhizosphere is a hotspot for denitrification. The nitrous oxide (N2O) reductase among denitrifiers and non-denitrifying N2O reducers is the only known N2O sink in the biosphere. We hypothesized that the composition of root-associated N2O-reducing communities when establishing on annual crops depend on soil type and plant species, but that assembly processes are independent of these factors and differ between nosZ clade I and II. Using a pot experiment with barley and sunflower and two soils, we analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…The copyright holder for this preprint this version posted November 4, 2022. ; https://doi.org/10. 1101/2022 Comparison between agricultural and wetland soils showed that targeted metagenomics detected substantially higher diversity of archaeal amoA genes than PCR amplicon sequencing, while, as expected, traditional metagenomics detected a lower diversity than either of those two methods (Fig. 4A).…”
Section: Comparison Between Targeted and Traditional Metagenomes And ...supporting
confidence: 56%
See 4 more Smart Citations
“…The copyright holder for this preprint this version posted November 4, 2022. ; https://doi.org/10. 1101/2022 Comparison between agricultural and wetland soils showed that targeted metagenomics detected substantially higher diversity of archaeal amoA genes than PCR amplicon sequencing, while, as expected, traditional metagenomics detected a lower diversity than either of those two methods (Fig. 4A).…”
Section: Comparison Between Targeted and Traditional Metagenomes And ...supporting
confidence: 56%
“…A reference phylogeny and alignment for nosZ was generated from full length nosZ amino acid sequences obtained from genomes downloaded from the NCBI genome database (accessed October 2019). A profile HMM for nosZ was generated from a previously published nosZ dataset (Graf et al, 2022), and then used to search translated open reading frames in downloaded genomes (e-value = 0.0001). Hits were then dereplicated at 99% amino acid similarity and aligned by amino acid using hmmalign within the HMMer suite (v.3.1.2).…”
Section: Phylogenetic Placement Of Nosz Reads From Shotgun and Probe ...mentioning
confidence: 99%
See 3 more Smart Citations